Disturbance-rejection-based tuning of proportional–integral–derivative controllers by exploiting closed-loop plant data. (May 2016) - Jeng, Jyh-Cheng; Ge, Guo-Ping
Abstract: A systematic data-based design method for tuning proportional–integral–derivative (PID) controllers for disturbance attenuation is proposed. In this method, a set of closed-loop plant data are directly exploited without using a process model. PID controller parameters for a control system that behaves as closely as possible to the reference model for disturbance rejection are derived. Two algorithms are developed to calculate the PID parameters. One algorithm determines the optimal time delay in the reference model by solving an optimization problem, whereas the other algorithm avoids the nonlinear optimization by using a simple approximation for the time delay term, enabling derivation of analytical PID tuning formulas. Because plant data integrals are used in the regression equations for calculating PID parameters, the two proposed algorithms are robust against measurement noises. Moreover, the controller tuning involves an adjustable design parameter that enables the user to achieve a trade-off between performance and robustness. Because of its closed-loop tuning capability, the proposed method can be applied online to improve (retune) existing underperforming controllers for stable, integrating, and unstable plants. Simulation examples covering a wide variety of process dynamics, including two examples related to reactor systems, are presented to demonstrate the effectiveness of the proposed tuning method. Highlights: Data-based approach for closed-loop tuning of PID controllers based on disturbance rejection. Two algorithms with immunity against noise are developed to calculate PID parameters. The tuning method is applicable to stable, integrating, and unstable plants. The proposed method is more effective than the model-based tuning methods. Applications to simulated reactor systems demonstrate the practicality of the method.